Additional saturday occupational therapy for adults receiving inpatient physiotherapy rehabilitation: a prospective cohort study - Erin L. Caruana; David Rowell; Suzanne S. Kuys; Sandra G. Brauer (BMC, 2022)
Abstract Background The first aim of this study was to investigate the impact of providing an additional four hours of Saturday occupational therapy to patients receiving Saturday physiotherapy in an inpatient setting on length of stay, functional independence, gait and balance. The second aim was to conduct an economic evaluation to determine if the introduction of a Saturday occupational therapy service in addition to physiotherapy resulted in a net cost savings for the rehabilitation facility. Methods A prospective cohort study with a historical control was conducted in an Australian private mixed rehabilitation unit from 2015-2017. Clinical outcomes included the Functional Independence Measure (Motor, Cognitive, Total), gait speed (10 Meter Walk test) and five balance measures (Timed Up and Go test, Step test, Functional Reach, Feet Together Eyes Closed and the Balance Outcome Measure of Elder Rehabilitation). Economic outcomes were rehabilitation unit length of stay and additional treatment costs. Results A total of 366 patients were admitted to the rehabilitation unit over two 20-week periods. The prospective cohort (receiving Saturday occupational therapy and physiotherapy) had 192 participants and the historical control group (receiving Saturday physiotherapy only) had 174 participants. On admission, intervention group participants had higher cognitive (p < 0.01) and total (p < 0.01) Functional Independence Measure scores. Participation in weekend therapy by the intervention group was 11% higher, attending more sessions (p < 0.01) for a greater length of time (p < 0.01) compared to the historical control group. After controlling for differences in admission Functional Independence Measure scores, rehabilitation length of stay was estimated to be reduced by 1.39 (p = 0.08) days. The economic evaluation identified potential cost savings of AUD1,536 per patient. The largest potential savings were attributed to neurological patients AUD4,854. Traumatic and elective orthopaedic patients realised potential patient related cost savings per admission of AUD2,668 and AUD2,180, respectively. Conclusions Implementation of four hours of Saturday occupational therapy in addition to physiotherapy results in a more efficient service, enabling a greater amount of therapy to be provided on a Saturday over a shorter length of stay. Provision of multidisciplinary Saturday rehabilitation is potentially cost reducing for the treating hospital.